Kedudukan Dan Prosedur Amdal Dalam Pengelolaaan Lingkungan Hidup - Muchamad Taufiq (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2011)
Dimiciling and Proscedure Analyse Concerning Impact Environment (AMDAL) in Management of Environment Expected. Attendance of Code/Law Number 23 Year 1997 about Management of Environment Expected to bring fresh wind in Environment Area Law of National commencing from the date of 19 September 1997. Code/Law Number 23 Year 1997 this here in after more knowledge with “UUPLH”. Have is common / pulic is existence of a activity of development besides affecting positive lso can give negatif impact. Where as government as owner of attribution to give or refuse a application of environment permit shall have clear standart. Activity of development which more and more to mount to contain contamination risk and mutilation of environment so that elementary function and structure of ekosistem becoming supporter of life can destroy. Contamination and mutilation of that environment will represent sosial burden, which is on finlly government and society have to account the exp[ense of its cure. One of the fundamental condition a environmental permit can be published to development plan industrial and any construction which have been arranged clearly is Making of Document of AMDAL (PP No. 27 Year 1999). Target of management of environment conducted to : preventing negatif impact, overcoming and controlling negatif impact of arising out and improve positive impact so that the impact give big benefit. Reality in field to point out that existence of AMDAL as condition application of environmental permit do not be executed better. For example all “pemrakarsa” tend to conduct former construction aktifitas, newly Document of AMDAL made. Condition that way not true, because Document of AMDAL, RKL and of UPL represent pregnant and environmental guide instrument of agreement meaning when coming into contact with other society. When problem appear on field, hence Document of AMDAL become importantly. Gift procedure of permit become “channel structure” which must be paid attention. When Document of AMDAL not yet been made, on the basis of what governmental publish permit ? Exactly exsistence of Document of AMDAL will very assisting